EXPLORING HAIKU IN STUDENTS’ ENGLISH CREATIVE WRITING AT SMA NEGERI 7 KOTA KUPANG - Mega, Sonya Kore; Marpaung, Tiarma; Metboki, Yakob (Journal of Language, Education, Literature, and Culture, 2023)
Getting challenged with academic writing, creative writing in a form of poetry can be delivered as an alternative task to help students cope with writing challenges. Haiku as one of the simplest poetry writings from Japan may help beginner writers to explore poetic words on certain objects or topics without using too many words in each line. Struggling writers can also use Haiku to stimulate their creative thinking in descriptive writing. With its simple pattern, Haiku can also boost students’ confidence to write. This study investigated whether students’ Haiku writing follows its rules and represents the qualities of creative writing. This qualitative study took 20 students in their third year of senior high school as research participants. This research used documentation as an instrument which is the students’ Haiku poetry writing. In the data analysis, students’ Haikus were assessed based on Haiku rules and the qualities of creative writing. It was found that most students have a sufficient understanding of the rules of Haiku writing. Students made some mistakes in their Haikus. However, students showed their efforts to perform the qualities of creative writing. Thus, the researchers believe that with consistent practices, students can write a qualified haiku as creative writing. More use of sensory words can further help the students to vary the diction and characterize the image described in their haikus. Finally, using haiku to express students’ feelings and thoughts and stimulate students’ creative writing is recommended in EFL classrooms.